Work pressure, job satisfaction and auditor turnover: Evidence from Vietnam - Quoc Thuan Pham; Thi Giang Tan Tran; Thi Ngoc Bich Pham; Luan Ta (Cogent Business & Management, 2022)
The research aims to determine the factors that explain auditor's decision to leave the audit profession. We employ a mixed approach of both qualitative and quantitative methods. A qualitative study is firstly performed using focus groups with the audit professionals to explore any new determinant(s) of auditor turnover in the Vietnam environment. The focus group indicates a new factor-the pressure of holding the Professional Certificate (CPA certificate)-that likely increases auditor turnover. A quantitative study is then conducted using survey method with a sample of 197 responses from current and former audit staff working for Vietnamese audit firms. We find that the perceptions of the profession, work conditions, work environment, and professional certificate pressure are associated with decisions to leave the audit profession. More importantly, professional certificate pressure-the emergent determinant-is the most influencing factor of auditor turnover. Some practical implications for policy makers to retain experienced and competent audit staff are also proposed.
Keywords: 650; auditor turnover; perceptions of the profession; professional certificate pressure; work conditions; work environment